Political Aspirations in India: Evidence from Fertility Limits on Local Leaders - S Anukriti; Abhishek Chakravarty (Institute for the Study of Labor (IZA), 2015)
Despite theoretical advances, measurement issues have impeded empirical research on aspirations. We quantify political aspirations in a developing country by estimating individuals' willingness to trade-off family size for political candidacy. Utilizing quasi-experimental variation in legal fertility limits on village council members in India, we find that at least 2.21% of married couples of childbearing age altered their fertility to remain eligible for council membership. This implies that returns to local leadership in low-income democracies are potentially high. Poorer, less educated, and lower-caste families display strong political aspirations, thereby lowering the extent of elite-capture at the local level of governance.
Keywords: J13; J16; H75; O11; 330; India; Panchayat elections; political aspirations; fertility limits; sex ratios